Dampak Kualitas Produk, Kualitas Pelayanan, Dan Kepercayaan Pelanggan Terhadap Loyalitas Pelanggan: Studi Pada Evanur Cards Surabaya - I Gede Wiyasa; Achmad Daengs GS; Rina Dewi; Diana Zuhro; Tjandra Wasesa (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Marketers generally want that the customers they create can be maintained forever. This is not an easy task considering that changes can occur at any time, both changes in customers such as tastes and psychological aspects and changes in environmental conditions that affect the psychological, social and cultural aspects of customers (Dharmmesta, 1999). Marketing strategies that aim to create and maintain customer loyalty include marketing strategies that are oriented towards long-term relationships (relationship marketing). The first understanding of relationship marketing lies in its difference with discrete transactions. Discrete transactions emphasize a short-term relationship pattern. While relationship transactions emphasize more on long-term relationship patterns (Gronhaug, et al., 1999). Berry and Parasuraman (1992) consider that relationship marketing is an effort to attract, develop and strengthen relationships between two parties. The parties involved are not limited to the relationship between producers and sellers, but also to the relationship between producers and service users. While Morgan and Hunt (1994) look more at all activities directly related to compiling, developing, and maintaining reciprocal relationships between service providers and service users.